The Historic Kitchen Restoration, the Example of Ham House: Part II - Davidson, Caroline (Petits Propos Culinaires, 2024)
In PPC 12 (November 1982) Caroline Davidson described the different sources of information she used to find out the contents of the kitchen at Ham House during the 1670s and 80s. It was during these two decades that the house enjoyed its greatest prosperity, under Elizabeth, Countess of Dysart and her second husband, the Duke of Lauderdale, Secretary of State for Scotland to Charles II. The kitchen was one of the most advanced of its time in England. It is now largely restored and open to the public, along with an adjacent larder and a passageway leading to the service courtyard. In this follow-up article, Caroline Davidson explains how she discovered what the objects in the kitchen looked like and also how they were made. For, in restoring the kitchen for the Victoria and Albert Museum, she pursued a dual policy of buying genuine 17th century objects and, when these could not be found, of commissioning craftspeople to make accurate reproductions.